PENANAMAN NILAI-NILAI DALAM PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI DI PPT NUSANTARA SAMBIKEREP SURABAYA - Siswoyo; Ahmad Pandu Winata; Mohammad Fahrudi Noer (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Abstract This study aims to identify the Islamic religious values instilled, the method of instilling them, as well as the supporting and inhibiting factors in the process at PPT Nusantara Sambikerep Surabaya. Islamic religious education is recognized for its urgency in early childhood development as a moral and spiritual foundation, relevant to the Indonesian context and the crucial role of PAUD in character building. Through a case study, this research found that PPT Nusantara applies various methods such as exemplary, playing in centers, storytelling, self-habituation, and demonstration. Supporting factors include student potential and educator competence, while inhibiting factors include parental awareness and teacher creativity. The conclusion shows that PPT Nusantara actively seeks to instill the basics of Islamic teachings to shape the character of noble early childhood.